ĐKXĐ: \(\left\{{}\begin{matrix}0\le x\le\frac{1}{2}\\0\le y\le\frac{1}{2}\end{matrix}\right.\) \(\Rightarrow xy\le\frac{1}{4}\)
Từ pt đầu: \(\Leftrightarrow\frac{4}{1+2xy}=\left(\frac{1}{\sqrt{1+2x^2}}+\frac{1}{\sqrt{1+2y^2}}\right)^2\le2\left(\frac{1}{1+2x^2}+\frac{1}{1+2y^2}\right)\)
\(\Leftrightarrow\frac{2}{1+2xy}\le\frac{1}{1+2x^2}+\frac{1}{1+2y^2}\)
\(\Leftrightarrow\frac{1}{1+2x^2}+\frac{1}{1+2y^2}-\frac{2}{1+2xy}\ge0\)
\(\Leftrightarrow\frac{2\left(2xy-1\right)\left(x-y\right)^2}{\left(1+2x^2\right)\left(1+2y^2\right)\left(1+2xy\right)}\ge0\) (2)
Do \(xy\le\frac{1}{4}< \frac{1}{2}\Rightarrow2xy-1< 0\)
\(\Rightarrow\left(2\right)\) xảy ra khi và chỉ khi \(x-y=0\Leftrightarrow x=y\)
Thế vào pt dưới:
\(2\sqrt{x\left(1-2x\right)}=\frac{2}{9}\Leftrightarrow x\left(1-2x\right)=\frac{1}{81}\Leftrightarrow...\)